Theory of communicative action: Lifeworld and systems, a critique of functionalist reason - Habermas. Jurgen; McCarthy, Thomas (UK Polity Press, 1989)
This study offers a systematic reconstruction of the theoretical foundations and framework of critical social theory. It is Habermas' "magnum opus", and it is regarded as one of the most important works of modern social thought. In this second and final volume of the work, Habermas examines the relations between action concepts and systems theory and elaborates a framework for analyzing the developmental tendencies of modern societies. He discusses in detail the work of Marx, Durkheim, G.H. Mead and Talcott Parsons, among others. By distinguishing between social systems and what he calls the "life-world", Habermas is able to analyze the ways in which the development of social systems impinges upon the symbolic and subjective dimensions of social life, resulting in the kind of crises, conflicts and protest movements which are characteristic of advanced capitalist societies in the late-20th century.
Keywords: Critical social theory; Modern societies; Social life